Power optimization control of small-sized wind turbine for Malaysia wind condition - Samsuri, Suhaila (2014)
This thesis presents ‘Power optimization control of a small-sized wind turbine for Malaysia wind condition.’ The study involves the small-sized (6kW) Stall-Regulated Variable-Speed Wind-Turbine (SRVSWT) with Squirrel Cage Induction Generator (SCIG) to compete the performance of existing Variable-Pitch Variable-Speed Wind-Turbine (VPVSWT). Nowadays, the VPVSWTs are widely used for modern wind turbines since they can produce better power regulation than the Fixed-Speed Stall-Regulated Wind-Turbine (FSSRWT). However, VPVSWT has some drawbacks such as more complexes and costly, heavier due to the requirements of extra electronic devices and also requires higher maintenance costs. Therefore, in this study, the Linear Quadratic Regulator (LQR) controller is proposed to improve power regulation of the SRVSWT system by maximizing its power generation along the low wind speed conditions (from the ‘cut-in’ to the ‘rated’ wind speeds). Using LQR controller, power can be regulated better by controlling the generator torque by controlling the stator and rotor current of the SCIG. Results show that the LQR controller is capable to regulate the maximum power generation in response to the instantaneous wind speed variations. Comparative study has been performed with the classical Proportional and Integral (PI) controller that uses speed loop control method. The comparative results indicate that the proposed LQR controller performs better power tracking performance than PI controller. However, in terms of speed loop tracking performance, the PI controller demonstrates faster speed tracking than the LQR. Too faster response however, would stress the wind turbine generator. Overall, LQR controller performs better power regulation with reasonable speed response through the generator torque control which is feasible to optimise the wind turbine operation suitable for Malaysia wind conditions. Thus, lighter, simpler and cheaper wind turbine can be used not only in Malaysia, but also in locations with low wind velocities.